Wabi-sabi and Self-cultivation in the process of creating the Yuba Community fashion design collection (ModaPalavra e-periódico, 2021)
This article aims to discuss the presence of traditional Japanese wabi-sabi aesthetic in the Yuba Community collection, by the Japanese-Brazilian fashion designer Fernanda Yamamoto. The experience with this agricultural community formed by Japanese-Brazilians, located in the city of Mirandópolis, São Paulo, supported by the tripod "cultivate the land, love the arts and pray" and refers to the processes of creation and production of the pieces of the parade and the photos which encompass the core of the presentation of this work. The wabi-sabi aesthetic relates to the beauty that erupts from simplicity and the course of time, variables that are identified in the processes of the work in question.
Keywords: fashion design; Fernanda Yamamoto; Yuba Communit